Solubility of soy lipophilic proteins: comparison with other soy protein fractions. Issue 4 (3rd April 2017) - Sirison, Jiraporn; Matsumiya, Kentaro; Samoto, Masahiko; Hidaka, Hiroshi; Kouno, Mitsutaka; Matsumura, Yasuki
Abstract: Solubility of soy lipophilic proteins (LP) was studied as compared with that of other soy protein fractions. LP, β-conglycinin, glycinin, and soy protein isolate (N-SPI) were prepared under the condition to avoid heat denaturation. Solubility of LP was lower than that of other soy protein fractions under all the tested conditions varying in pH values and ionic strength. The solubility of LP was increased constantly by elevating temperature until 90 °C, whereas that of β-conglycinin and glycinin dropped at high temperature. Temperature-dependent change in solubility of N-SPI might reflect the balance among that of glycinin, β-conglycinin and LP. Based on the results of SDS-PAGE, determination of phospholipid content and Fourier Transform Infrared spectroscopy, we discussed the solubilization behavior of LP relating to its origin and composition. Graphical abstract: : Solubility of SPI is determined by the balance among that of glycinin, -conglycinin and LP.